2017
DOI: 10.1016/j.applthermaleng.2016.11.079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extreme wetting scenarios on pool boiling conditions

Abstract: ManuscriptClick here to download Manuscript: Teodori et al_ETFS_12ev.docx Click here to view linked References  Detailed pool boiling bubble dynamics on extreme wetting regimes is performed  Under extreme wetting regimes, wettability plays a dominant role  "Quasi-Leidenfrost" regime is supported by comparison with theoretical predictions  The macro-contact angle can be used in correlations predicting bubble size  Apparent angles should not be approximated to quasi-static values for predictions

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 35 publications
2
19
0
Order By: Relevance
“…The radial temperature profiles were obtained after post processing the IR images using a custom made, in-house developed MatLab code which allowed conversion of the raw IR images to temperature data. The high speed images were used to evaluate the spreading diameter i.e., the contact diameter and impact velocity using a code previously developed MatLab [40]. An example of the IR post processed images, temperature profiles as well as the raw and post-processed high speed images, is shown in Figure 3.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…The radial temperature profiles were obtained after post processing the IR images using a custom made, in-house developed MatLab code which allowed conversion of the raw IR images to temperature data. The high speed images were used to evaluate the spreading diameter i.e., the contact diameter and impact velocity using a code previously developed MatLab [40]. An example of the IR post processed images, temperature profiles as well as the raw and post-processed high speed images, is shown in Figure 3.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…In this state, droplets also have high static contact angles, but are strongly pinned in place due to high contact angle hysteresis [22,23]. In boiling, superhydrophobic surfaces have commonly been shown to transition to film boiling upon incipience, rendering them useless in application despite having favorable incipience superheats [29][30][31][32][33]. Recently, however, the authors have demonstrated the ability to limit vapor spreading during boiling on superhydrophobic surfaces by bringing these surfaces into the Wenzel state prior to boiling [34].…”
Section: Introductionmentioning
confidence: 99%
“…Textured superhydrophilic surfaces have shown significant enhancement of CHF through capillary wicking, albeit with delayed incipience and moderately reduced heat transfer coefficients during boiling; they have been thoroughly investigated for high-heat-flux boiling applications [5,20,21]. Conversely, superhydrophobic surfaces have been observed to drastically reduce the critical heat flux, often immediately transitioning to film boiling at boiling incipience, with little or no nucleate boiling observed, as summarized in Table I [22][23][24][25][26]; despite any potential increase in the heat transfer coefficient, the narrow range of nucleate boiling operation has precluded consideration of superhydrophobic surfaces for practical boiling applications. In an attempt to utilize the favorable boiling characteristics of hydrophobicity, without the concomitant reduction in CHF, heterogeneous surfaces have recently been proposed that add hydrophobic regions to act as nucleation sites on hydrophilic surfaces [27,28]; in some cases, simultaneous improvement in the heat transfer coefficient and CHF has been observed compared to uniform hydrophilic surfaces [29][30][31].…”
mentioning
confidence: 99%